METAPHOR ANALYSIS IN SONGS LYRICS OF CHARLIE PUTH: A CASE ON SEMANTICS - Monika Pardede; Christina Natalina Saragi; Usman Sidabutar (Sean Institute, 2023)
In this study, the types of metaphors found in Charlie Puth's song lyrics are analyzed. This study aims to investigate issues like (1) What types of metaphors are employed in each of the Charlie Puth songs' lyrics? (2) What are the dominant metaphors types used in Charlie Puth's lyrics songs? Finding the many kinds of metaphors used in Charlie Puth's song lyrics is the goal of this study. According to Goatly's (1997:136) hypothesis, there are six different categories of metaphor namely: Active metaphor, Inactive metaphor, Asymmetric metaphor, Subjective metaphor, Dead metaphor, and Mimatic metaphor. This study's analysis of the data is qualitative and descriptive in nature. The source of the data was song lyrics by Charlie Puth. The tools used to gather the data were observational and documentary tools. The data collection method involved finding the song lyrics by Charlie Puth and transcribing the information. According to this study, there are 82 different types of data metaphors present in Charlie Puth's song lyrics, including the following: Active metaphor (9,75%), Inactive metaphor (14,63%), Asymmetric metaphor (24,39%), Subjective metaphor (19,51%), Dead metaphor (20,73), and Mimatic metaphor (10,97%). The researcher deduced from the findings that the most prevalent metaphor in Charlie Puth's song lyrics is an asymmetric metaphor.